2017
DOI: 10.1074/jbc.m117.794453
|View full text |Cite
|
Sign up to set email alerts
|

Conformational memory in the association of the transmembrane protein phospholamban with the sarcoplasmic reticulum calcium pump SERCA

Abstract: The sarcoplasmic reticulum Ca-ATPase SERCA promotes muscle relaxation by pumping calcium ions from the cytoplasm into the sarcoplasmic reticulum. SERCA activity is regulated by a variety of small transmembrane peptides, most notably by phospholamban in cardiac muscle and sarcolipin in skeletal muscle. However, how phospholamban and sarcolipin regulate SERCA is not fully understood. In the present study, we evaluated the effects of phospholamban and sarcolipin on calcium translocation and ATP hydrolysis by SERC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…Several proteins display conformational memory, where the protein transiently keeps its active conformation after the dissociation from its former binding partner [13]. Examples include the active state of the endocytosed, unliganded integrin receptor [14], as well as the SERCA Ca-ATP-ase [15]. Here, we propose that conformational memory may participate in the molecular memory formation of single cells (Figure 1).…”
Section: Conformational Memorymentioning
confidence: 84%
See 1 more Smart Citation
“…Several proteins display conformational memory, where the protein transiently keeps its active conformation after the dissociation from its former binding partner [13]. Examples include the active state of the endocytosed, unliganded integrin receptor [14], as well as the SERCA Ca-ATP-ase [15]. Here, we propose that conformational memory may participate in the molecular memory formation of single cells (Figure 1).…”
Section: Conformational Memorymentioning
confidence: 84%
“…--Intrinsically disordered proteins (IDPs): proteins that do not have an ordered 3dimensional structure; in many proteins, structural disorder only extends to a segment (intrinsically disordered region, IDR) of the protein. [13][14][15]. For example, the integrin receptor (β1 subunit) [14], SERCA Ca-ATP-ase [15], and prion-like proteins [3,20,21] all possess conformational memory and participate in cellular learning.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the PLN effect on ATP-dependent Ca 2+ translocation by SERCA, SSM-based current measurements were carried out on co-reconstituted proteoliposomes containing SERCA and PLN [ 57 ]. The proteoliposomes were adsorbed on the SSM and activated by Ca 2+ and/or ATP concentration jumps.…”
Section: P-type Atpases Investigated On Solid Supported Membranesmentioning
confidence: 99%
“…The results from pre-steady state charge (calcium) translocation experiments were compared with steady-state measurements of ATPase hydrolytic activity. It was found that the PLN effect on SERCA transport activity depends on substrate conditions, and PLN can establish an inhibitory interaction with multiple conformational states of SERCA (a calcium-free E 2 state, a E 1 -like state promoted by Ca 2+ , and a E 2 -like state promoted by ATP, shown in red in Figure 4 ) with distinct effects on SERCA’s kinetic properties [ 57 ]. It was also noted that once a particular SERCA–PLN inhibitory interaction is established, it remains throughout the SERCA transport and catalytic cycle.…”
Section: P-type Atpases Investigated On Solid Supported Membranesmentioning
confidence: 99%
“…While the application of a variety of simulation and experimental approaches alone has led to a greater insight into the mechanisms for SERCA-PLB regulation, the structural changes induced by Ca 2+ and how those are communicated to couple enzymatic activity with active transport remain poorly defined. More specifically, it remains unknown whether binding of a single Ca 2+ ion initiates SERCA-PLB activation by stabilizing the transport sites [17,22,23] and producing a SERCA structure that is compatible with Ca 2+ binding [24], or by inducing large-scale domain arrangements that produce catalytically competent conformations of SERCA [25,26]. Answering these questions requires knowledge of the structural changes and motions at high spatiotemporal resolution.…”
mentioning
confidence: 99%